Tularemia Outbreak, Bulgaria, 1997–2005 - Todor Kantardjiev; Ivan Ivanov; Tzvetan Velinov; Plamen Padeshki; Boris Popov; Roumiana Nenova; Milcho Mincheff (Emerging Infectious Diseases, 2006)
The 1997–2005 tularemia outbreak in Bulgaria affected 285 people. Ten strains were isolated from humans, a tick, a hare, and water. Amplified fragment length polymorphism typing of the present isolates and of the strain isolated in 1962 suggests that a new genetic variant caused the outbreak.